Parathyroid Carcinoma – An Uncommon Differential Diagnosis of Pathological Bone Fracture - Kantamani Bala Teja; Shivakumar Thiagarajan; Munita Menon (Journal of Head & Neck Physicians and Surgeons)
We present a case of an unusual presentation of parathyroid carcinoma. A women in her 40s presented with pathological fracture without any other symptom. All her investigations pointed towards an abnormally functioning parathyroid gland. The abnormally function parathyroid gland was localised and subsequently the patient underwent surgical removal of the same. The final histopathological diagnosis was that of a parathyroid carcinoma.